Assessing the Association of Sodium, Potassium Intake and Sodium/Potassium Ratio on Blood Pressure and Central Adiposity Measurements amongst Ellisras Undernourished, Rural Children Aged 5-13 Years: South Africa - Thato Tshepo Raphadu; Moloko Matshipi; Peter Modupi Mphekgwana; Kotsedi Daniel Monyeki (MDPI AG, 2022)
Background: Numerous studies have shown how diet, such as sodium (Na) and potassium (K) intake, is an important risk factor for non-communicable diseases (NCDs). This study aimed to assess the relationship between sodium intake, potassium intake; and sodium/potassium ratio with blood pressure (BP) and abdominal obesity amongst Ellisras rural children. Method: In this cross-sectional study, data on dietary intake of sodium and potassium were collected using a 24-h recall questionnaire from a total of 765 participants, aged 5-13 years. Blood pressure and anthropometric measurements were also collected. Generalised linear models and Pearson correlation were conducted to assess the association of sodium intake, potassium intake; and their ratio with BP, waist circumference (WC), and waist-to-height ratio (WHtR). Results: In both age groups, less than 14.9% of males and 19.8% of females consumed above the recommended adequate intake (AI) of sodium. In addition, both age groups had more than 90% of males and females who consumed below the recommended AI of potassium. Moreover, the sodium/potassium ratio was above the WHO recommended level in more than 30% of males and females. The study found a significant, weak positive correlation of sodium intake with systolic BP (SBP), diastolic BP (DBP), and with WHtR. A significant, weak positive correlation was also found between sodium/potassium ratio and WHtR. In addition, a significant association was found between potassium intake and systolic BP. Conclusion: Although our study found a notable low average intake of sodium and potassium as compared to the recommended values. There was positive correlation found between sodium intake and BP. Furthermore, a positive correlation of sodium intake and sodium/potassium ratio with WHtR was also found.